Raman specroscopy as appropriate tool for chemical discrimination of wild hemp oil seed samples - Pećinar, Ilinka; Rančić, Dragana; Špirović Trifunović, Bojana; Božić, Dragana (Acta herbologica, 2024)
Wild hemp (Cannabis sativa L. ssp. sativa var. spontanea Vavilov), as a whole plant, especially its seeds are highly valued, with significant place in the production of oil-based paints, in creams as a moisturizer, for cooking, animal and bird feed. This work represents an innovative report focused on the evaluation of the phytochemical composition of wild hemp seeds grown in two different locations in Serbia, using Raman microspectroscopy in combination with multivariate data analysis. Some significant differences were found between the analyzed oil samples in terms of chemical profile. The Raman spectra of the wild hemp seed samples indicate the predominance of unsaturated (1657 and 1268 cm-1), then saturated fatty acids (1443, 1306 and 1084 cm-1) and fatty acid esters (1745 cm-1) due to the higher intensity of the bands. The relative intensities of these bands may indicate that the seed oil of wild hemp from two different locations differs in the content of unsaturated and saturated fatty acids, as shown by the differences in the relative intensities of 1657 and 1268 cm−1.